UMNO : Satu Kajian Kelangsungan Parti Politik Melayu - Shahidan, Kassim (2006)
This thesis analyzes the survival of UMNO politics in the governing of Malaysia within the context of the new millennium. The objectives of this research are also to identify the extent of the peoples' support towards UMNO in the coming elections and to recognize the factors that influenced these peoples' support. Beside that, this research exposes the opportunities, strengths, threats and weaknesses of UMNO in their journey of survival of past and the future Malay politics. Generally, there is a balance of finding between quantitative and qualitative analysis through hypothesis testing that have been established. Based on previous researches [plasser, F., (2001), Chamil Wariya (1998), Coleman, J. J., (1996), Ahmad Fawzi Basri., et.all (1995), Ahmad Atory Hussain (1990,1998) Baharudin Ali Masrom (1989), Syed Arabi & Safar (1986) and others] this research found the existence of several factors as determinants of the peoples' support towards UMNO. The hypothesis testings that have been carried out in the research confirms all factors (candidate and leadership, party programmes, image and ideology, democracy, economic growth, issue and campaigns factors) have a positive correlation with the peoples' support towards UMNO. In order to evaluate UMNO's future political survival, history can be used as a yardstick, as well as for forecasting and making some observations. In previous elections, such as the election of 1978, 1982, 1986, 1990, 1999 and 2004, Barisan Nasional (BN) and UMNO have always won with a big majority or achieved a high percentage of votes. As a dynamic and growing party the last sixty (60) years, UMNO has always faced challenges from within and outside the organization itself. The challenges occurred due to the existence of external factor and factors within the party. There are several suggestions which must be given due consideration by UMNO especially, and the Malays, generally , to ensure its survival in the future. Amongst others is the prerequisite for UMNO to preserve its influence amongst the Malays, which is dependent on its willingness to hold on tight to the core struggle of upholding the Malay rights. Other than that, UMNO has to fulfill other important prerequisites such as, having an efficient and transparent administration, planning effective development programmes, as well as the encouraging Malay professionals to join the party but must continue to support government of the day. Professionals ought to be given a change to air their objections and opinions. Meanwhile those who give opinions different from that of the leadership should not be sidelined For the sake of the future of the Malay race and Islam, UMNO and its leaders need to be strongly united, and at the same time the must be really credible and of good character. To ensure its honorable struggle can be carried on, UMNO needs to be led by personalities who are clean and respected, and upholding Islamic principles. They should be chosen from the ranks of intellectuals, whilst leaders with unhealthy practices should be cast aside. The leaders should be brave and sincere, putting party struggle above their own needs. They should lead and treat equally all groups within UMNO, and not choose their own groups to benefit while they are power. Hence there is a lot that must be borne by a leader to the extent of sacrificing the ultimate for the sake of the Malays, religion and the nation.